Constitutional Protection for Ownership Owners Who Reject Consignation - Richo Fernando Sitorus; Tahegga Primananda Alfath (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
This research aims to analyze the legis ration of granting consignment for development in the public interest and to analyze the constitution providing legal protection for owners of land rights who refuse consignment. This research is a normative legal research with a statutory approach. The legal material analysis technique used in this research is to use descriptive techniques. The results showed that the legis ratio of consignment provisions was based on the social function of land rights as regulated in Article 6 of Law Number 5 of 1960 concerning Basic Agrarian Regulations. The consignment itself is regulated in Article 42 of the Land Acquisition Law. The constitution provides legal protection for owners of land rights who refuse consignment because it is the community's right to get the protection enshrined in the 1945 Constitution and Pancasila as the philosophy of life of the nation and as the Ideology of the Unitary State of the Republic of Indonesia. In the 1945 Constitution Article 28H paragraph (4) states that "every person has the right to have private property rights and such property rights may not be taken arbitrarily by anyone".